ANALISIS TERHADAP PERUBAHAN SALINITAS AIR TANAH DANGKAL PADA SISTEM AKUIFER TAK TERTEKAN CEKUNGAN JAKARTA - Indriatmoko, Robertus Haryoto (Jurnal Air Indonesia, 2016)
The study on ground water salinity changes in unconfine aquifer system, is the study of hydrostatic equilibrium between the fresh ground water and salty ground water, aquifer unconfine restricted to coastal. The main objective of the aspects examined, namely: (i) To identify the level of intrusion of sea water in the basin aquifer system taktertekan Jakarta. The purpose and methodology of the study are as follows: (i) The primary data (1995-2009) and secondary (2010), including salinity data attributes, including ground water level, coordinates (UTM) and groundwater salinity levels (ii). Regression analysis of the relationship between the data (EC, Cl- and TDS). (Iii). Analysis of the period 1995-2010 salinity map using GIS and graphic analysis. (Iv). The focus of the analysis in three zones transection (ZT), namely ZT-I west, ZT-II central and eastern ZT-III was unconfine aquifer system in the Jakarta basin. The conclusion of this study are: (i) Variable Cl- and TDS have a strong correlation to predict EC using the following equation Y = 3.45 X + 517.80 (R2 = 0.88) for the DHL and TDS = 1, 86 X + 132.86 (R2 = 0.99) , (ii) based on the results of the analysis of the level of sea water intrusion during the period 1995-2010 (15 years), the intrusion of sea water has reached 8 km from the coast in the ZT-III, in ZT-II reaches 5 km and at ZT-I at 4.8 km from the coastal. Analysis of the development of the distance from shore limit saltwater intrusion since 1982 for 28 years can be calculated that the rate of salt water intrusion in the transection zone I is 0.1 km/year, the transection zone II is 0.06 km/year and in the zone transecting III is 0.11 km/year. The main cause of major intrusion of sea water into the aquifer system of the mainland is the amount of groundwater pumping against excessive.Keywords : Ã‚Â salt water intrusion, unconfine aquifer, aquifer system, Jakarta basin, recharge, salinity, electrical conductivity.